OUTCOMES OF LAPAROSCOPIC CHOLECYSTECTOMY COMBINED WITH COMMON BILE DUCT EXPLORATION FOR THE TREATMENT OF CONCOMITANT GALLBLADDER AND COMMON BILE DUCT STONES AT PHU THO PROVINCIAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the early outcomes of laparoscopic cholecystectomy combined with common bile duct exploration and intraoperative choledochoscopy for choledocholithiasis at Phu Tho Provincial General Hospital.Methods: A cross-sectional descriptive study was conducted on 39 patients diagnosed with concomitant gallbladder stones and common bile duct stones.Results: From June 2022 to June 2025, a total of 39 patients underwent one-stage laparoscopic surgery at Phu Tho Provincial General Hospital. The conversion rate to open surgery was 5.2%, the stone clearance rate was 94.8%, and the postoperative complication rate was 7.7%, including one case (2.6%) requiring reoperation. No mortality was recorded.Conclusion: One-stage laparoscopic cholecystectomy combined with common bile duct exploration using intraoperative choledochoscopy is a feasible and safe procedure at the provincial hospital level. However, larger studies are needed to further validate its effectiveness.
Keywords: Biliary stones, Laparoscopic cholecystectomy, laparoscopic common bile duct exploration